Development of an Expert System for Crisis Risk Assessment in Bullying Cases to Support School Counselor Service Protocols: Expert Validation and System Feasibility Testing - Andi Tenri Aunia Sabir; Imam Nur Ihsan Mustafa; Ince St Aisyah Tri Utami; Irda Baenaha; Isbahuddin; Jihan Aprilia Patata (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
Bullying in school environments has increasingly led to psychological crises among students, requiring early detection and structured risk assessment by school counselors. However, risk assessment practices are often subjective and lack standardized digital support systems. This study aims to develop an expert system for crisis risk assessment in bullying cases to support school counseling service protocols through expert validation and system feasibility testing. The research employed a Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. During the analysis phase, crisis risk indicators were identified through literature review and needs assessment with school counselors. The design and development phases produced a rule-based expert system utilizing weighted scoring to classify risk levels into low, moderate, and high categories. Expert validation involving counseling, psychology, and information systems specialists indicated a feasibility score of 88% (very feasible). User feasibility testing with school counselors resulted in an acceptance rate of 84% (feasible to highly feasible). System accuracy testing showed an accuracy rate above 80% compared to manual assessments. The findings demonstrate that the developed expert system is valid, feasible, and effective as a decision support tool for assessing crisis risk in bullying cases. This study contributes to the integration of counseling science and artificial intelligence by providing a structured, objective, and protocol-based digital assessment system to enhance school crisis management services